IMPLEMENTATION OF THE ALPHABET REFORM IN PRISONS - Mehmet KÖÇER (Fırat University, 2019)
The issue of changing the alphabet, which was raised mainly by the intelligentsia at the final period of the Ottoman Empire, was suspended. Mustafa Kemal Pasha, an Ottoman Army Officer, ignited the War of Independence, relying on the sincerity of the people of Anatolia. Mustafa Kemal Pasha thought it was not possible to win the war only relying on military training; and advocated that a bigger war would be won by bringing the whole public to a desired level in terms of education and teaching. He took every opportunity to state that the war against ignorance was more effective and important than any other war. After winning the War of Independence, a new administration was established and the Republic of Turkey was proclaimed. One of the most important and effective Dynamics of the Republican regime was the issue of education and teaching. Mustafa Kemal Pasha took every occasion to underline the important of education; and introduced the issue of changing the alphabet when also the favourable conditions started to emerge. This issue, which had been raised for a long time by the intelligentsia, was considered not only by the government but also by the state. Language and writing was regarded as an important pillar of education and training activities because the vast majority of Anatolian people were not literate. Furthermore, Mustafa Kemal Pasha had come to the conclusion that lack of education was in the core of the collapse of the Ottoman Empire. For this reason; his first priority was to ensure that a new alphabet was eloped which was easy to write and read, which had its spelling rules and which was contemporary. As a result, a new Turkish Alphabet was created, composed of Latin letters. The long awaited change of alphabet was then officially conducted.